2012
DOI: 10.1016/s0140-6736(12)61380-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial catheters for reduction of symptomatic urinary tract infection in adults requiring short-term catheterisation in hospital: a multicentre randomised controlled trial

Abstract: UK National Institute for Health Research Health Technology Assessment Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
172
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(178 citation statements)
references
References 15 publications
3
172
0
3
Order By: Relevance
“…[9][10][11][12][13][14][15] These studies have examined endpoints such as bacteriuria and symptomatic CA-UTI, or surveillance-defined UTI. 8,16,17 In a study by Pickard et al, 17 noble metal alloy catheters were found to be ineffective in reducing the incidence of symptomatic surveillance-defined UTI when used in short-term (mean, 2 days) surgical patients and they did not support the routine use of these catheters in this patient group. Lack of effect is not surprising due to the short catheterisation time and low-risk patient group.…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13][14][15] These studies have examined endpoints such as bacteriuria and symptomatic CA-UTI, or surveillance-defined UTI. 8,16,17 In a study by Pickard et al, 17 noble metal alloy catheters were found to be ineffective in reducing the incidence of symptomatic surveillance-defined UTI when used in short-term (mean, 2 days) surgical patients and they did not support the routine use of these catheters in this patient group. Lack of effect is not surprising due to the short catheterisation time and low-risk patient group.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as soon as the antibiotic contained in the device is exhausted, antibiotic delivery stops. Antibioticcoated surfaces have also been studied in animal and clinical studies of urinary catheters, endotracheal tubes, orthopedic devices, and vascular grafts, with contrasting clinical benefits (205)(206)(207)(208)(209)(210)(211)(212)(213)(214)(215)(216). Thus, development of a coated surface that prevents bacterial colonization for a long time remains a challenge.…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…Of these, only nitrofurazone-impregnated catheters and catheters with hydrophilic and/or silver alloyimpregnated coatings have reached the U.S. market; these have shown mixed results (29)(30)(31)(32)(33)35). However, a recent study by Pickard et al (36) found that neither silver alloy-nor nitrofurazonecoated catheters significantly reduced CAUTIs in a clinical study of patients with short-term catheterization, and the clinical data are currently considered insufficient to strongly recommend their use in standard practice (16).…”
mentioning
confidence: 99%